Antibacterial, phytochemical and GC-MS analyses of argel (Solanum argel) leaves: Biological characteristics of Solanum argel - Abdelgadir Abdelmuhsin, Abdelmuhsin; Ibrahim, Safa Mustafa; Kehail, Mutaman Abdelgadir; Sulieman, Abdel Moniem Elhadi (Cellular and Molecular Biology, 2024)
Finding novel, efficient antimicrobial drugs is crucial in this age of pressing global health challenges. The medicinal qualities of the leaves of the argel plant (Solanum argel, or S. argel) have been recognized in traditional medicine for quite some time. The medicinal potential of these leaves may be due to the presence of bioactive substances such as alkaloids, flavonoids, and phenolic acids. S. argel leaf antibacterial, phytochemical, and gas chromatography–mass spectrometry (GC–MS) characteristics are the focus of this investigation. To conduct the study, bioactive compounds would be extracted from the leaves and tested against a panel of bacterial pathogens. Then, the compounds would be identified using GC-MS analysis. Mean inhibition zones of 15.30±1.0 mm, 14.67±0.42 mm, 15.0±0.01 mm, and 15.56±0.22 mm for the bacteria E. coli, Staph. aureus, and Sal. typhimurium, respectively, were seen in the antibacterial results at a concentration of 3 µg/disc. Secondary metabolites such as alkaloids, flavonoids, phenolic substances, and tannins were identified using phytochemical investigation. Antimicrobial, antioxidant, and anti-inflammatory are just a few of the many bioactivities associated with these phytochemicals. Argel plant leaves contain bioactive chemicals that show they could be a source of new pharmaceuticals. Argel leaves were analyzed using GC-MS and 37 different chemicals were found. The most abundant compounds were 4H-Pyran-4-one and 2,3-dihydro-3.5-hydroxy, followed by 3-Pentanol, 2,2,4,4-tetramethyl, and 2,2-Dimethyl-3-[3-methyl-5-(phenylthio)-, with areas of 11.80%, 10.6%, and 9.47%, respectively. The analysis was performed within a time range of 5.070 to 34.464 minutes. According to the research, Argel leaf has powerful antioxidant and antibacterial capabilities, making it an excellent substance for medical and food preservation applications.